Influencia de los problemas intrafamiliares en el proceso académico de los/las estudiantes del Instituto Artesanal Arenillas, de la ciudad de Arenillas periodo lectivo 2012-2013. - Aguilar Rodríguez, Freddy Ronald (2013)
The development of the research was oriented depending on the influence of family problems in the academic process of students in the teaching institute Artisan Arenillas, the canton Arenillas, problematic context that affects the academic process of students. On the other hand, related to the qualitative and quantitative methods approach was used for the operationalization of the investigation. The research was field, bibliographic and documentary survey was also applied to teachers and students, information that facilitated the verification of hypotheses. They were processed and analyzed the data obtained, which allowed to know the reality of the object of research results used in the proposed proposal. the findings and the respective recommendations, which justified the investigative process was determined.